Characterization and phylogenetic analysis of the chloroplast genome of Solanum pseudocapsicum (Solanaceae) - Yongle Liu; Xuan Tang; Aihua Deng; Huan Li; Yulong Xiao; Wenyan Zhao; Lixuan Xiang; Yi Liu; Zui Yao; Xingyu Zeng; Zhitian Du; Rongjie Huang; et al. (Mitochondrial DNA. Part B. Resources)
Solanum pseudocapsicum Linnaeus 1753, a popular indoor potted plant known for its ornamental fruits, had its chloroplast genome sequenced in this study to determine its phylogenetic relationship with other related species and to construct a phylogenetic analysis tree. The research findings are as follows: 1. The chloroplast genome of S. pseudocapsicum comprises a large single-copy (LSC) region of 86,260 base pairs, a small single-copy (SSC) region of 18,325 base pairs, and two inverted repeat (IR) regions, each measuring 25,390 base pairs in length. 2. The G + C content of the entire chloroplast genome is 37.59%, with the highest G + C content found in the IR regions, reaching 43.03%; followed by the LSC region, which has a G + C content of 35.68%; and the lowest in the SSC region, with a G + C content of 31.53%. 3. The genome contains 127 genes, including 82 protein-coding genes, 37 tRNA genes, and 8 rRNA genes, with 18 genes duplicated in the IR regions. 4. Phylogenetic analysis revealed that S. pseudocapsicum, Solanum betaceum, Solanum laciniatum, and Solanum nitidum are genetically closely related and are located on the same branch of the phylogenetic tree, indicating a close relationship among them. This study provides a foundation for the identification, classification, and exploration of genetic diversity within the Solanum genus.